Data and archives: challenges for a profession shaken by digital transformation - Moro-Cabero, Manuela [UNESP] (My University, 2021)
The article presents the confluence of data and archives in the face of the digital transformation and investigates the main changes, considering reality, emerging problems and new risks and opportunities. The research is descriptive and analytical based on scientific literature. It analyses the impact on the archivist’s object of work and the interrelationships in data, information and document management systems. The reuse of solid information and datacentric trends prevails, motivated by the potential of the technologies.
Datos y archivos Retos para una profesión agitada por la transformación digital
Dados e arquivos: desafios para uma profissão abalada pela transformação digital
Keywords: data; digital archival science; digital transfor-mation; records management